Successful treatment of refractory checkpoint inhibitor‐induced hepatitis with quadruple therapy including extracorporeal photopheresis and infliximab - Inga Hansen; Julian Kött; Silke Heidenreich; Francis A. Ayuk; Patricia Doll; Finn Abeck; Nina Booken; Christoffer Gebhardt; Stefan W. Schneider (Wiley, 2024)
Abstract Immune checkpoint inhibitors have established in the treatment of malignant melanoma and have significantly improved prognosis in advanced tumour stages. As they interfere with immunoregulatory pathways by blocking checkpoints, nonspecific activation of the immune system can result in the development of immune‐related adverse events. Hepatitis occurs in 25%-30% of combination therapy and usually occurs 6-12 weeks after initiation of treatment. In most cases, the adverse event can be successfully treated with glucocorticosteroids but sometimes this is not sufficient, and further therapy is required. We report on a life‐threatening course of immune‐mediated hepatitis in a 39‐year‐old woman with metastatic melanoma, whom we were finally able to treat successfully with a combination therapy consisting of prednisolone, mycophenolate‐mofetil, extracorporeal photopheresis and infliximab.